Evaluation of the posterior airway space following orthopaedic treatment of mandibular deficient Class II malocclusion - a pilot study - Costello Christopher J; Sambevski John; Cheng Lam L; Darendeliler M. Ali (Sciendo, 2018)
The use of Twin Block therapy is a well-accepted functional treatment option for the correction of a Class II malocclusion. In addition to skeletal and dental changes, its use may also promote changes in airway structure and dimension, including the size of the posterior airway space (PAS). This may be of importance in reducing the risk of developing obstructive sleep apnoea syndrome (OSAS).